ІННОВАЦІЙНІ ПІДХОДИ ДО ПРОЦЕСУ ФОРМУВАННЯ ТВОРЧИХ ПРОФЕСІЙНИХ УМІНЬ МАЙБУТНІХ УЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2009)
The article covers the problem of forming of creative professional abilities of future teachers; opens up using the innovative methods of teaching, the pedagogical terms of forming of creative activity of future teacher are summarized.